The Impact of Internal Marketing on Educators' Satisfaction and Loyalty in Private Universities - Helmi, Sulaiman; Sartika , Dewi; Ramadhina, Shafira Fitri; Fitriani, Rosha (Ilomata International Journal of Management, 2025)
This study examines the impact of Internal Marketing on customer satisfaction and loyalty, emphasizing its role in fostering long-term customer relationships. The research addresses the extent to which Internal Marketing influences these outcomes, particularly in competitive markets. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze survey data. Validity and reliability tests were conducted to ensure the robustness of the results. Findings indicate that Internal Marketing significantly influences both customer satisfaction and loyalty, with a stronger effect on satisfaction. These results underscore the strategic importance of Internal Marketing in enhancing customer-related outcomes. Businesses can utilize these insights to develop more effective internal marketing strategies aimed at improving customer satisfaction and loyalty.